2017
DOI: 10.15517/rbt.v65i1-1.31687
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive cycle of the sea cucumber (Isostichopus fuscus) and its relationship with oceanographic variables at its northernmost distribution site

Abstract: The brown sea cucumber Isostichopus fuscus is highly prized and intensively fished, yet no studies of its reproductive cycle at its northernmost distribution site exist. To characterize its reproductive cycle, monthly surveys (Oct 2014-Dec 2016) that included gonad collection were conducted in 118 sites along the eastern coast of Baja California, including islands from Bahía San Luis Gonzaga (29o 49’ 14.18” N, 114 o 3’56.17” W) to the 28th parallel north. A total of 2 808 sea cucumber specimens were measured (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Shiell & Uthicke (2006) also found that in Holothuria whitmaei the males and females' ratio did not differ from unity in a population of Western Australia (N = 325), but in a population of Pacific Australia more males than females predominated significantly (N = 206). Something similar happened also happens with the species Isostichopus fuscus in two populations of Mexico (Pañola-Madrigal et al, 2017). Another species of the same genus (Holothuria tubulosa) was studied in the Aegean Sea (N = 166) by Kazanidis et al (2010) and in the Adriatric sea (N = 130) by Despalatović et al (2004), both obtained the same result (1:1) regarding the sex ratio.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…Shiell & Uthicke (2006) also found that in Holothuria whitmaei the males and females' ratio did not differ from unity in a population of Western Australia (N = 325), but in a population of Pacific Australia more males than females predominated significantly (N = 206). Something similar happened also happens with the species Isostichopus fuscus in two populations of Mexico (Pañola-Madrigal et al, 2017). Another species of the same genus (Holothuria tubulosa) was studied in the Aegean Sea (N = 166) by Kazanidis et al (2010) and in the Adriatric sea (N = 130) by Despalatović et al (2004), both obtained the same result (1:1) regarding the sex ratio.…”
Section: Discussionsupporting
confidence: 64%
“…Despite the fact that the sex ratio is 1:1 in most holothurians (Ramofafia, Byrne & Battangle, 2001;Asha & Muthiga, 2008;Fajardo-León et al, 2008;Kazanidis et al, 2010; Peters-Didier, Pardo, Garrido & Gallardo, 2018;Cahuzac et al, 2019), as in the Ría de Vigo, some species demonstrated an unbalanced ratio (Costelloe, 1985;Navarro et al, 2012;Omar, Abdel Razek, Abdel Rahman & El Shimy, 2013;Pañola-Madrigal, Calderón-Aguilera, Aguilar-Cruz, Reyes-Bonilla & Herrero-Pérezrul, 2017). In fact, Santos et al (2016) found in H. forskali, more female than males; these authors explain that the place of sampling is subject to strong tides which is considered to be another major factor affecting the balanced sex ratio due to the fact that strong sea waves often promote species´ evisceration as a stress response.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations